THE LABOR-INVESTIGATIVE FORMATION AS INTEGRATIVE MAIN DISCIPLINE IN THE PRIMARY TEACHER’S INITIAL FORMATION - Fernández Artiles, Omara Eugenia; Fundora Martínez, Carlos Luis (Atenas, 2015)
The process of the primary teacher’s initial formation should favor the student’s preparation for its professional acting, with a development of pedagogic professional abilities and a professional focus, with character developer, interdisciplinary, investigative and problematizador. In this context, the Labor-investigative Formation is considered as integrative main discipline, that which presupposes that you/they are integrated contents of the different disciplines of the study plan in its system of knowledge. Presently work establishes theoretical bases about this Cuban conception with a view to reaching the ways of professional performance that we aspire.